Trabectedin and lurbinectedin: Mechanisms of action, clinical impact, and future perspectives in uterine and soft tissue sarcoma, ovarian carcinoma, and endometrial carcinoma - Gadducci, Angiolo; Cosio, Stefania (Frontiers in Oncology, 2022)
TThe ecteinascidins trabectedin and lurbinectedin are very interesting antineoplastic agents, with favorable toxicity profile and peculiar mechanisms of action. These drugs form adducts in the minor groove of DNA, which produce single strand breaks [SSB]s and double strand breaks [DSB]s and trigger a series of events resulting in cell cycle arrest and apoptosis. Moreover, the ecteinascidins interact with tumor microenvironment, reduce the number of tumor associated macrophages and inhibit the secretion cytokines and chemokines. Trabectedin has been approved by Federal Drug Administration [FDA] for patients with unresectable or metastatic liposarcoma or leiomyosarcoma who received a prior anthracycline-based regimen. Moreover, trabectedin in combination with pegylated liposomal doxorubicin [PLD] has been approved in the European for the treatment of platinum-sensitive recurrent ovarian cancer. Lurbinectedin has been approved by FDA for patients with metastatic small cell lung cancer with disease progression on or after platinum-based chemotherapy. The review assesses in vitro and in vivo experimental studies on the antineoplastic effects of both ecteinascidins as well as the clinical trials on the activity of trabectedin in uterine sarcoma and ovarian carcinoma and of lurbinectedin in ovarian carcinoma and endometrial carcinoma